Compliance with the Adversarial Principle During Deviation From Charges: A Case Study of Georgia - Latsabidze, Giorgi (European Scientific Journal, ESJ, 2025)
In accordance with the first part of Article 9 of the Criminal Procedure Code of Georgia (CPCG), from the moment of commencement of criminal prosecution, criminal proceedings are conducted based on the adversarial principle and the equality of arms. Part two of Article 25 of the same Code states that the collection, presentation, and examination of evidence fall within the competence of the parties, and the court does not participate in this process, except in rare cases. This paper addresses the following issue of whether a court, on its own initiative, may qualify a charge and find a person guilty of an action that the prosecution does not dispute at all. Specifically, when the court independently intervenes in the qualification of the claim, does it violate the principle of CPCG. How should such actions by the court be understood, and, in general, does the court have the right to find a person guilty of an offense that the prosecution has not disputed throughout the entire process?! The study examines both the approach of the European Court on this matter and the practice of national courts regarding the reclassification of the claim, particularly what the court considers a deviation from the charge and the range of the reclassification of the charge. The article also includes a discussion of applicable legal norms and judicial practice and provides conclusions.